The Effect of Changes in The Shoreline of The Sea Law Implementation in West Rangsang Subdistrict, Kepulauan Meranti District - Hendra Yosep Siburian; Rifardi; Afrizal Tanjung (Faculty of Fisheries and Marine, Universitas Riau, 2020)
This research was conducted in October 2018 at the West Rangsang Beach Waters, Meranti Islands Regency, Riau Province. This study aims to determine changes in shoreline that occurred in West Rangsang Sub-District in the last 10 years and the implementation of marine law regarding the regulation of shoreline change problems. Results of processing Landsat 5 and Landsat 8 images with large Changes in the coastline in the Melai Village were 55.56 m (accretion), in the Village of Kedabu Rapat as much as 50.94 m (abrasion) and in the village Bungur at 42.10 m (abrasion). The implementation of the law of the sea according to article 15 of UNCLOS 1982 in the determination of territorial sea areas adjacent to other countries decided the law No. 2 of 1971 concerning the determination of the borders of the two countries in the Malacca Strait. Determination of these coordinates are based on the baseline of each country. With the enactment of the 1982 International Law on the Law of the Sea, the Republic of Indonesia Government Regulation No. 38 of 2002 stipulated a list of geographical coordinates of the baseline points of the Indonesian archipelago. With the determination of geographical coordinates the problems in the changes in the coastline of the countries of Indonesia and Malaysia as a result of abrasion and accretion can be solved by observing the geographical coordinate points on the island of Rangsang